Artificial breakwaters as garbage bins: Structural complexity enhances anthropogenic litter accumulation in marine intertidal habitats. (July 2016) - Aguilera, Moisés A.; Broitman, Bernardo R.; Thiel, Martin
Abstract: Coastal urban infrastructures are proliferating across the world, but knowledge about their emergent impacts is still limited. Here, we provide evidence that urban artificial reefs have a high potential to accumulate the diverse forms of litter originating from anthropogenic activities around cities. We test the hypothesis that the structural complexity of urban breakwaters, when compared with adjacent natural rocky intertidal habitats, is a driver of anthropogenic litter accumulation. We determined litter abundances at seven sites (cities) and estimated the structural complexity in both urban breakwaters and adjacent natural habitats from northern to central Chile, spanning a latitudinal gradient of ∼15° (18°S to 33°S). Anthropogenic litter density was significantly higher in coastal breakwaters when compared to natural habitats (∼15.1 items m −2 on artificial reefs versus 7.4 items m −2 in natural habitats) at all study sites, a pattern that was temporally persistent. Different litter categories were more abundant on the artificial reefs than in natural habitats, with local human population density and breakwater extension contributing to increase the probabilities of litter occurrence by ∼10%. In addition, structural complexity was about two-fold higher on artificial reefs, with anthropogenic litter density being highest at intermediate levels of structural complexity. Therefore, the spatial structure characteristic of artificial reefs seems to enhance anthropogenic litter accumulation, also leading to higher residence time and degradation potential. Our study highlights the interaction between coastal urban habitat modification by establishment of artificial reefs, and pollution. This emergent phenomenon is an important issue to be considered in future management plans and the engineering of coastal ecosystems. Graphical abstract: Abstract : The structural complexity contributes to the high accumulation and residence time potential of anthropogenic litter observed on urban breakwaters compared with natural habitats.